Anti-Alopecia Activity of Coumarin Derivatives Isolated from Merremia peltata Leaves and Computational Study of Their Binding to Androgen Receptors Using Molecular Docking and Molecular Dynamic Simulation - Syawal Abdurrahman; Ruslin Ruslin; Aliya Nur Hasanah; Mus Ifaya; Resmi Mustarichie (MDPI AG, 2023)
Alopecia is a condition in which hair on the scalp or other areas of the body is lost or falls out excessively. Nutritional deficiency causes blood flow to the head to decrease causing the hormone testosterone to be changed by the enzyme 5-α-reductase to dihydrotestosterone, which inhibits the growth phase and accelerates the death phase. One of the methods developed to treat alopecia is through inhibition of the 5-α-reductase enzyme, which converts testosterone to its more potent metabolite, dihydrotestosterone (DHT). Ethnomedicinally, Merremia peltata leaf is used by the people of Sulawesi as a remedy for baldness. Therefore, in this research, an in vivo study was conducted on rabbits to determine the anti-alopecia activity of M. peltata leaf compounds. The structure of the compounds isolated from the M. peltata leaf ethyl acetate fraction was determined by analysis of NMR and LC-MS data. An in silico study was then carried out using minoxidil as a comparison ligand; scopolin (1) and scopoletin (2) isolated from M. peltata leaf were identified as anti-alopecia compounds by predicting docking, simulating molecular dynamics and predicting absorption, distribution, metabolism, excretion, and toxicology (ADME-Tox). Compounds 1 and 2 had a better effect on hair growth compared to positive controls, and NMR and LC-MS analysis showed that they had comparable binding energies to receptors in the molecular docking interaction study: −4.51 and −4.65 kcal/mol, respectively, compared to −4.8 kcal/mol for minoxidil. Molecular dynamics simulation analysis with the parameters binding free energy calculated using the MM-PBSA method and complex stability based on SASA, PCA, RMSD, and RMSF showed that scopolin (1) has a good affinity for androgens receptors. The ADME-Tox prediction for scopolin (1) showed good results for the parameters of skin permeability, absorption and distribution. Therefore, scopolin (1) is a potential antagonist to androgen receptors and could be useful in the treatment of alopecia.